Penafsiran Lafadz Rahmat dalam Tafsir Al Maraghi - Khoiriyah, Khoiriyah; Sulthoni, Akhmad; Amrulloh, Muhamad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research examines the interpretation of the term